The Effect of Absolute versus Relative Temperature on Health and the Role of Social Care - Giuliano Masiero; Fabrizio Mazzonna; Michael Santarossa (Institute of Labor Economics (IZA), 2021)
We investigate the effect of extreme temperatures on mortality and emergency hospital admissions, and whether local social care allows to mitigate their adverse effects. We merge monthly administrative data on mortality and hospital discharge from Italian municipalities for the period 2001-2015 with daily data on local weather conditions, and yearly data on disaggregated municipal expenditure. We compare two different measures of temperature shocks, the standard measure based on absolute levels and another measure based on deviations from local mean temperatures. We find that the former measure is more effective in capturing the adverse effects of shocks on health outcomes. In particular, extremely hot and cold days increase mortality rates and hospital admission rates for both cardiovascular and respiratory diseases. These effects are mostly driven by the oldest age group and partially by young children. Then, we report evidence of a mitigating effect of social expenditure on the impact of extremely hot and cold days on both emergency hospital admission and mortality rates. A back of the envelope calculation suggests that the additional social care expenditure is fully compensated by the benefits arising from the lower impact of temperature shocks.
Keywords: I18; Q51; Q54; 330; hospital admissions; mortality; social expenditure; temperature shocks